If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = -3x + x + 3 Reorder the terms: -9 = 3 + -3x + x Combine like terms: -3x + x = -2x -9 = 3 + -2x Solving -9 = 3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -9 + 2x = 3 + -2x + 2x Combine like terms: -2x + 2x = 0 -9 + 2x = 3 + 0 -9 + 2x = 3 Add '9' to each side of the equation. -9 + 9 + 2x = 3 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 3 + 9 2x = 3 + 9 Combine like terms: 3 + 9 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| ((32x^3)-(28x^2)-47x-12)=0 | | (-5/2x)+(3/4x)=(-3/4) | | 2(-1-1x)=-26 | | ((32x^3)-(28x^2)-47x-12)/(8x+3) | | 2x+7=4x+65/9 | | 7x+1=-3x-19 | | -2x+2-x=32 | | 4x+2-x=29 | | 8x-2(x+5)-7+5x=-21+4+x | | 10+4x-x=64/7 | | 8x-2(x-5)-7+5x=21+3x | | -3+4x-7x=21 | | 118=4(20)+38 | | 8d-3/5=5d+3/2 | | 51=2x+7x+6 | | p=23/3(18) | | 106/5=7x+4x-4/5 | | p=7(18) | | 10x+7=20x | | p=6(18) | | 6a-4a-5=7a-23 | | -7x+6x=-2 | | (7u-4v-2)(2u+1)=0 | | x+10=9-1 | | -2x-2-2x=26 | | Y=50.8y | | p=5(18) | | Y=50+8y | | 46=4x+38 | | -2=5x-x-2 | | 3=-2x+6x+7 | | p=44/9(20) |